Design and analysis of remote monitoring and testing of telephone for highways - Hushairi, Bin Hj. Zen (Universiti Malaysia Sarawak, UNIMAS, 2001)
This thesis presents a design of a circuitry that enables highway telephones to be tested and monitored from remote offices. Research survey on remote monitoring and testing of telephone system for highways and its roles in providing road users in time of emergencies are also discussed.